Identification of the seasonal conditions required for dormancy break of Persoonia longifolia (Proteaceae), a species with a woody indehiscent endocarp - Chia, K.A.; Sadler, R.; Turner, Shane; Baskin, C.C. (2016)
Background and Aims: The mechanisms involved in breaking seed dormancy in species with woody endocarps are poorly understood. In a landmark study examining the role of endocarps in regulating germination, our aim was to investigate the effects of the natural sequence of environmental conditions on dormancy break of a species with a woody endocarp (Persoonia longifolia).